Proteoliposome Engineering with Cell‐Free Membrane Protein Synthesis: Control of Membrane Protein Sorting into Liposomes by Chaperoning Systems. Issue 10 (23rd August 2018) - Ando, Mitsuru; Schikula, Shun; Sasaki, Yoshihiro; Akiyoshi, Kazunari
Abstract: Integral membrane proteins (IMPs) modulate key cellular processes; their dysfunctions are closely related to disease. However, production of IMPs in active conformations for further study is hindered by aggregation and toxicity in living expression systems. IMPs are therefore produced in cell‐free systems employing liposome chaperoning, but membrane integration of the nascent IMPs is suboptimal and orientation of the integrated proteins remains uncontrollable. Thus, an artificial membrane protein sorting system is developed, based on polyhistidine/nickel‐chelate affinity, combined with cell‐free membrane protein synthesis. Its proof of concept is demonstrated with a N‐terminal hexahistadine‐fused conexin‐43 (NHis–Cx43) model IMP. Nickel‐chelating liposomes efficiently incorporate twofold newly synthesized NHis–Cx43 compared with Cx43. NHis–Cx43, when synthesized in this system, forms dye‐permeable hemichannels, similar to plasma membrane pores formed by Cx43 in cells. The topology of incorporated NHis–Cx43 indicates two orientations in the liposomal membranes. However, NHis–Cx43 orientation is controlled, resulting in single topology, by combination of the natural molecular chaperone DnaKJE. Successful synthesis and at least 4.5‐fold increase lipid incorporation are also achieved with three other NHis‐fused IMPs, including α‐helix and β‐barrel IMPs. Overall, this simple membrane protein sorting system is usable combined with molecular chaperones to prepare proteoliposomes for many applications. Abstract : An artificial membrane protein sorting system is developed based on cell‐free N‐terminal hexahistidine‐fused membrane protein synthesis in the presence of nickel‐chelating liposomes, inspired by endogenous translocon‐mediated protein sorting systems. Addition of a natural molecular chaperone in this system can control the orientation of the protein in the liposomal membrane.